Perthionitrite-Induced Persulfidation in Binuclear Cobalt(II) Complexes - Anuj Baran Chakraborty; Rajib Hazra; Amit Majumdar (Journal of the American Chemical Society, 2026)
Abstract Persulfidation of sulfhydryl functional group (-SH) in protein and nonprotein thiols is a physiologically important process and generally involves the reduction of a partially oxidized sulfur by a fully reduced sulfur. In the present work, two dicobalt(II)-nitrito complexes, [Co2(PhBIMP)(μ-NO2)(DMF)]2+ (2) and [Co2(PhBIMP)(μ-NO2)2]1+ (3), have been demonstrated to react with RC(O)SH (R = Me, Ph) to generate the persulfidated complexes, [Co2(PhBIMP)(μ-SSC(O)R)]2+ (R = Me, 5a; Ph, 5b) in high yields (65–72%) along with nitric oxide (71–80%). Characterization of all the products and intermediates by structural and spectroscopic methods, and comparison of the results with those obtained from control experiments, established the generation of [Co2(PhBIMP)(μ-SC(O)R)(MeCN)]2+ (R = Me, 4a; Ph, 4b) and perthionitrite (SSNO–) in the reactions of 2/3 with RC(O)SH, followed by persulfidation of the coordinated thiocarboxylate (RC(O)S–) in 4a and 4b by the in situ generated SSNO– to produce the persulfidated complexes, 5a and 5b, respectively. The present work thus demonstrates, for the first time, that SSNO–, a physiologically relevant S/N-crosstalk species, can effectively mediate the persulfidation of sulfhydryl functional groups and may implicate a similar, but hitherto unknown, role of SSNO– in biological persulfidation processes.